INHIBISI XANTIN OKSIDASE OLEH FRAKSI ETIL ASETAT DARI DAUN JARUM TUJUH BILAH (Pereskia bleo (Kunth) D.C) SEBAGAI ANTIHIPERURISEMIA - Sari, Prinka Susmita; Sitorus, Saibun; Gunawan, Rahmat (Jurusan Kimia FMIPA UNMUL, 2018)
“Jarum Tujuh Bilah” leaves (Pereskia bleo (Kunth) DC) are a medicinal plant that often used in traditional medicine to reduce uric acid levels. This plant contains secondary metabolites which have the potential to inhibit xanthine oxidase activity. In this study phytochemical tests were conducted on ethanol extract and ethyl acetate fraction of “Jarum Tujuh Bilah” leaves (Pereskia bleo (Kunth) DC), then isolated xanthine oxidase from fresh cow's milk, and the activity of ethyl acetate fraction against xanthine oxidase. The results showed that ethanol extract contained flavonoid, alkaloid and phenolic compounds. Then ethyl acetate fraction contained flavonoid and alkaloid compounds. The value of xanthine oxidase activity from the isolation of xanthine oxidase is 0.00063 U/mL in the fractionated enzyme and 0.00025 U/mL in the supernatant. The inhibition of 92.06% ethanol extract and the inhibition of ethyl acetate fraction was 88.89%.